Prevalência e gravidade de lesões cervicais não cariosas e hipersensibilidade dentinária: associação com qualidade de vida entre adultos - Anna Rachel dos Santos Soares (2020)
The change in epidemiological profile of oral health thanks to the reduction of dental caries and periodontal disease, populations’ aging, and maintenance of teeth for longer have contributed to the arising of other oral conditions and their impact on quality of life (QoL). Amongst them, tooth wear on the cervical area of teeth, known as Non-Carious Cervical Lesion (NCCL), and Dentin Hypersensitivity (DH) related to dentine exposure, related or not to tooth wear, have a multifactorial etiology. There is a gap in the literature on population-based epidemiological studies that investigate the association between DH, in presence or not of tooth wear, and the presence of impacts on the QoL of individuals, taking into account possible confounding factors that may interfere with this association. The aim of the study was to assess the association between DH, presence or absence of NCCL and oral impacts on daily activities. A cross-sectional study was conducted between 2018 and 2019 with a probabilistic sample of adults (30 to 50 years old) residing in a small Brazilian city. Interview and epidemiological exam were performed by calibrated examiners (Kappa > 0.7). The dependent variable was the present of oral impacts, assessed by at least one impact “fairly often” and “very often” in one of daily activities, assessed by the validated version in Brazil of the Oral Health Impact Profile (OHIP-14). The Tooth Wear Index was used to assess the prevalence (codes 2, 3 and 4) and severity of NCCL. Tactile stimulus with probe in the cervical area of teeth was the method for DH diagnostic, with severity recording using a Visual Analogue Scale: mild (1-2); moderate (2-7); and intense (8-10). The combination of both clinical variables resulted in the following categories of independent variables: without NCCL, without DH; with NCCL, without DH; without NCCL, with DH; and with NCCL, with DH. The adjusted variables referred to sociodemographic data (age, sex and self-reported color), socioeconomic factors (education and monthly family income), habits and behaviors in health (use of medication, brushing frequency, diet, smoking and alcohol consumption) and oral health conditions (symptoms of temporomandibular disorders, dental caries and periodontal disease). Associations were investigated by crude and adjusted Poisson regression models using a Direct Acyclic Graph (Stata 17). Of the total sample of 197 adults, 59.3% (CI95%: 50,5 – 67,5) had impact of oral conditions in daily activities and 31.3% (CI95%: 22,7 – 41,4) had NCCL and DH, simultaneously. Higher frequency of impact on physical pain dimension was observed in adults with DH and NCCL (PR: 2.46; 95% CI: 1.21 - 5.00) and without LCNC (PR: 2.03; 95% CI: 1.21 - 3.41). Independently of presence or absence of NCCL, DH is perceived as a pain due to oral problems and can affect the food selection.